The Dual Role of Platelets in the Cardiovascular Risk of Chronic Inflammation - Zamora, Carlos; Cantó, Elisabet; Vidal, Sílvia (Frontiers in Immunology, 2021)
Patients with chronic inflammatory diseases often exhibit cardiovascular risk. This risk is associated with the systemic inflammation that persists in these patients causing a sustained endothelial activation. Different mechanisms have been considered responsible for this systemic inflammation and among them, activated platelets have been regarded as a major player. However, in recent years, the role of platelets has become controversial. Not only can this subcellular component release pro- and anti-inflammatory mediators, but it can also bind to different subsets of circulating lymphocytes, monocytes and neutrophils modulating their function in either direction. How platelets exert this dual role is not fully understood.